RESPONS TIME PERAWAT TERHADAP TINGKAT KECEMASAN DAN KEPUASAN PASIEN BPJS DI PUSKESMAS RAWAT INAP KABUPATEN INDRAGIRI HILIR - Muhammad Asyir Annur; Rini Harianti; Rendi Randika (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2023)
The emergency department (ED) has the aim of providing optimal health services to patients in handling the emergency level to prevent risks. The various types of diseases and patient conditions, as well as the number of visits that come together to the ED, have resulted in overcrowding in the ED so that appropriate and fast services are needed. The purpose of the study was to determine the response time of nurses to the level of anxiety and satisfaction of BPJS Health patients at the Inpatient Health Center, Indragiri Hilir Regency. The type of research is observational analytic with a cross-sectional design. The population in this study were all patients in 3 Inpatient Health Centers in Indragiri Hilir Regency as many as 217. The research sample consisted of 141 patients with the distribution of proportions at Gajah Mada Health Center 43 patients, Sungai Salak Health Center 43 patients, and Kotabaru Health Center 55 patients. Data analysis using chi-square test. The results showed that the majority of nurse response time was for 114 patients (80.85%), the response time to anxiety was p = 0.000, and the response time to patient satisfaction was p = 0.000. It was concluded that there was a significant relationship between the nurse's response time with the level of anxiety and satisfaction of BPJS Health patients in the emergency departments of the Inpatient Health Center, Indragiri Hilir Regency. It is suggested to the puskesmas to develop policies to improve the quality of health services in serving patients.